Chempaka by-election No sabotage by Umno, despite attacks - Borneo Post, (KK) (BorneoPost Online, 2015)
KOTA BAHARU: Despite being hurled with various accusations by the opposition parties, Umno remains professional and. did not sabotage the PAS candidate in the by election for the Chempaka state seat which ended on Sunday.